Effects of long-term consumption of two plant-based dietary supplements on cardiovascular health and low-grade inflammation in middle-aged and elderly people: study protocol for a randomised, controlled trial - Melina Tsiountsioura; Gerhard Cvirn; Lisa Meixner-Goetz; Tobias Ziegler; Manfred Lamprecht (BMC, 2023)
Abstract Background Ageing is a process characterised by chronic low-grade inflammation and oxidative stress which could lead to increased prevalence of both physical and mental age-related chronic conditions. A healthy balanced diet, rich in fruit and vegetables as well as omega-3 polyunsaturated fatty acids (n3 PUFA), could reduce oxidative stress and improve markers of low-grade inflammation. Nonetheless, considering that a large part of the population struggles to meet current guidelines on fruit and vegetable and n3 PUFA recommendations, fruit and vegetable concentrate supplements and mixed omega fatty acid supplements could be an effective strategy to bridge the gap between actual and recommended intakes. Methods In this randomised, controlled, open-labelled, parallel-grouped clinical trial, 112 participants will be allocated to one of four arms (n = 28 on each arm): an encapsulated juice powder concentrate, a plant-based omega fatty acid supplement, both or a control group. We aim to investigate whether long-term separate or combined ingestion of the two can affect biomarkers of cardiovascular health, low-grade inflammation and indicators of ageing, including cognitive function, in middle-aged and elderly people. We will additionally explore the effect of the different supplementations on plasma levels of vitamins, carotenoids and fatty acids. Intervention will last 2 years and participants will be assessed at baseline and at follow-up visits at 6, 12, 18 and 24 months. Discussion This study will provide evidence whether long-term, plant-based dietary supplementation can support cardiovascular health, anti-inflammatory processes, immunity and nutritional status in ageing. Trial registration This trial was registered at ClinicalTrials.gov (NCT04763291) on February 21, 2021.